España : sociedad, política y civilización : (siglos XIX-XX) / José María Jover Zamora, Guadalupe Gómez-Ferrer Morant, Juan Pablo Fusi Aizpúrua - Gómez-Ferrer Morant, GuadalupeFusi, Juan Pablo (1945-); Jover Zamora, José María (1920-2006) (Areté)
Bibliografía: p. 853-880